Experimental Investigation into Characteristics of Plasma Aerodynamic Actuation Generated by Dielectric Barrier Discharge - Yun, Wu; Yinghong, Li; Min, Jia; Huimin, Song; Changbing, Su; Yikang, Pu (Chinese journal of aeronautics, 2010)
This article carries out synthetic measurements and analysis of the characteristics of the asymmetric surface dielectric barrier discharge plasma aerodynamic actuation. The rotational and vibrational temperatures of an N2 （ C3 Ⅱu ） molecule are measured in terms of the optical emission spectra from the N2 second positive system. A simplified collision-radiation model for N2 （C）and N2 ＋ （B）is established on the basis of the ratio of emission intensity at 391.4 nm to that at 380.5 nm and the ratio of emission intensity at 371. 1 nm to that at 380.5 nm for calculating temporal and spatial averaged electron temperatures and densities. Under one atmosphere pressure, the electron temperature and density are on the order of 1.6 eV and 10H cm-3 respectively. The body force induced by the plasma aerodynamic actuation is on the order of tens of mN while the induced flow velocity is around 1.3 m/s. Starting vortex is firstly induced by the actuation ; then it develops into a near-wall jet, about 70 mm downstream of the actuator. Unsteady plasma aerodynamic actuation might stimulate more vortexes in the flow field. The induced flow direction by nanosecond discharge plasma aerodynamic actuation is not parallel, but vertical to the dielectric layer surface.